2017
DOI: 10.1160/th16-10-0769
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the 20-minute whole blood clotting test in detecting venom induced consumption coagulopathy from Russell’s viper (Daboia russelii) bites

Abstract: The 20-minute whole blood clotting test (WBCT20) is used as a bedside diagnostic test for coagulopathic snake envenoming. We aimed to assess the performance of the WBCT20 in diagnosis of venom induced consumption coagulopathy (VICC) in Russell's viper envenoming. Adult patients admitted with suspected snake bites were recruited from two hospitals. WBCT20 and prothrombin time (PT) test were performed on admission. WBCT20 was done by trained clinical research assistants using 1 ml whole blood in a 5 ml borosilic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 25 publications
0
49
1
Order By: Relevance
“…Although these tests are used as diagnostic tools, they may not be readily available in resource-poor and isolated settings. 16 Instead, bedside whole-blood clotting tests have been used as a cheaper alternative for standard laboratory tests, such as the 20-minute whole-blood clotting test (WBCT20). 3,16,17 The Lee-White clotting time (LWCT), originally developed to monitor patients with hemophilia, has been used nationwide both as a diagnosis tool of snake venom-induced coagulopathy and to monitor antivenom therapy efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Although these tests are used as diagnostic tools, they may not be readily available in resource-poor and isolated settings. 16 Instead, bedside whole-blood clotting tests have been used as a cheaper alternative for standard laboratory tests, such as the 20-minute whole-blood clotting test (WBCT20). 3,16,17 The Lee-White clotting time (LWCT), originally developed to monitor patients with hemophilia, has been used nationwide both as a diagnosis tool of snake venom-induced coagulopathy and to monitor antivenom therapy efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Dsilva et al observed that 24% of abnormal WBCT20 results were false-positive [4]. Rathnayake et al found that 13 of 908 snakebite patients with INR <1.4 had a false-positive WBCT20 [3]. In such situations, estimation of prothrombin time would be required.…”
Section: Discussionmentioning
confidence: 99%
“…Presence of regional lymphadenitis was also noted. One of the investigators (PS) performed a WBCT20 using a fresh clean borosilicate glass tube as described earlier [3]. Prothrombin time was tested in the clinical laboratory on blood samples collected into citrate tubes.…”
Section: Setting and Populationmentioning
confidence: 99%
See 2 more Smart Citations